Detection of Salmonella Enterica in Egg Yolk by PCR on a Microfluidic Disc Device Using Immunomagnetic Beads - Izumi Kubo; Mitsutoshi Kajiya; Narumi Aramaki; Shunsuke Furutani (Sensors, 2020)
Salmonella enterica is a pathogenic bacterium that causes foodborne illness. One of the vehicle foods of S. enterica are chicken eggs. Efficient collection of the bacterium is necessary to detect it specifically. We developed a method to detect S. enterica by PCR on a microfluidic disc device using a fluorescent probe. Salmonella enterica cells were isolated in the microchambers on the device, followed by thermal lysis and PCR targeting with the invA gene, a gene specific to S. enterica, were observed by measurement of the fluorescent signal that resulted from gene amplification. However, the developed method was unable to discriminate viable cells from dead cells. Consequently, in this study, magnetic beads modified with anti-Salmonella antibody were utilized to detect viable Salmonella cells from egg yolk prior to PCR on the device. While using the antibody-modified beads, egg yolk components, which inhibit PCR, were removed. The collected cells were subsequently detected by PCR of the invA gene on a microfluidic disc device. This method enabled the detection of viable cells without the inhibition of PCR by any egg component. S. enterica was detected at 5.0×104 cells mL−1 or at a higher concentration of egg yolk within 6 h including the sampling time.